2020
DOI: 10.14529/hsm19s208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Specialized Physical Education and Additional Aerobic Training on Aerobic Endurance of Police Students

Abstract: Aim. The aim of this study was to investigate if the SPE classes were sufficient to improve the police students’ aerobic endurance over the period of 12 weeks; and to investigate if two additional aerobic trainings per week may have an effect on the students’ aerobic endurance. Materials and Methods. An initial and final estimated maximal oxygen consumption of 233 (♀87 and ♂146) police students were assessed at the begging and after 12 weeks of training. All participants were performing SPE classes as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Both approaches are command-based, meaning that cadets do what, how and how much they are told to do. Although this is shown to improve cadets’ fitness [ 44 , 45 , 46 , 47 ], it is less likely to provide a long-term retention of cadets (later officers) in regular physical activity (PA) or exercise. Studies on police cadets and officers showed a reduction in PA and fitness with the time spent in service [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both approaches are command-based, meaning that cadets do what, how and how much they are told to do. Although this is shown to improve cadets’ fitness [ 44 , 45 , 46 , 47 ], it is less likely to provide a long-term retention of cadets (later officers) in regular physical activity (PA) or exercise. Studies on police cadets and officers showed a reduction in PA and fitness with the time spent in service [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, during their fourth year, cadets utilize the previously obtained knowledge by applying different training methods on their own. In more detail, curricula include three training classes mostly based on self-defense and use of force, while strength and conditioning take a small portion of curricula and includes teaching on basic methods of physical preparation [ 44 , 50 ]. In their junior year, cadets prescribe their own individualized exercise training program.…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness has been defined as the ability to complete daily activities without undue fatigue and with enough energy left for pursuing leisure activities [ 1 ]. The measurement of physical fitness is an important part of the recruitment and training process of police officers because the job ranges from physically non-demanding (i.e., administrative work) to highly demanding (i.e., chasing, arresting the belligerent or controlling a riot) [ 2 , 3 , 4 ]. Therefore, next to health-related physical fitness, performance-related physical fitness is also required in certain police occupations [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, once police trainees or students enter the police force, their physical fitness typically decreases while their body fat increases as they advance in their career, predominantly due to a lack of planned physical activity and poor nutrition [ 13 , 14 ]. Although socioeconomic, demographic, environmental and cultural factors could have an effect on physical fitness and body composition [ 15 , 16 , 17 ], the structure and the focus of strength and conditioning programs may be of importance as well [ 3 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation